A Global Overview of Poison Treatment Apps and Databases. (March 2019) - Poojari, Pooja G.; Thunga, Girish; Nair, Sreedharan; Kunhikatta, Vijayanarayana; Rao, Mahadev
Acute poisoning is a serious health problem that is associated with high mortality. Management of acute poisoning cases in the critical care settings is the biggest challenge due to the difficulty in identification of poison involved. Immediate information about the poisoning and its management is crucial in the early diagnosis, treatment, and in the prevention of poisoning complications. Poison information resources, such as various poison apps and databases, are essential for the retrieval of updated and quick information on poisoning. Through provision of information to the public and to health care professionals, apps and databases play a significant role in the management of poisoning cases.